RANCANG BANGUN ALAT PERCOBAAN MOMEN INERSIA DENGAN MENGGUNAKAN TIMER OTOMATIS - Hari Rizki Pratama; Riad Syech; Sugianto ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
A research has been conducted on designing of an automatic experiment ofmoment of inertia using a self-timer with a variation in radius of a cylinder as an inertialbody. This research was done using an experimental method and especially to design aself-timer calculation tools used in the experiment. The trial results showed that at 0.10m height average time for a cylinder rolling on an inclined plane with a slope of 2.87°for 2 m length could be represented by the regression equation that is y = 0.031x +0.400. Based on the result of the experiment, the coefficient of the moment of inertiaranged from 0.509 to 0.523 with a percentage error ranged from 1.800% to 4.600% andstandard deviation of experimental time measured from 0.011 to 0.034 seconds.